Quality of Birth Certificate Processing Services Based On Klampid New Generation in Kedung Cowek Urban Village, Surabaya City - Atikah, Irma Inas Azzah; Umiyati, Sri (Universitas Muhammadiyah Tapanuli Selatan, 2025)
lack of public awareness makes the level of birth certificate processing low, the village itself rarely conducts socialisation about the importance of population administration, inadequate facilities in the services carried out run less smoothly. The research objective is to describe and analyse the quality of birth certificate processing services based on Klampid New Generation in Kedung Cowek Village, Surabaya City. The type of research to be used is descriptive research with a qualitative approach So to complete the definition of variables in this study, the authors are guided by the theory revealed by Parasuraman with 5 dimensions of service quality, namely: Tangible (Direct Evidence), Reliability, Responsiveness, Assurance, Empathy. The indicators in this study are five dimensions, namely Tangibles, Reliability Dimensions, Responsiveness Dimensions, Assurance Dimensions, Empathy Dimensions. Based on the results of research conducted on the quality of birth certificate services based on klampid new generation in Kedung Cowek City Village, the quality of public services, especially birth certificate services based on klampid new generation, has good quality because there is no delay when uploading files, but when the application is updated from the centre it will hamper online services